Validasi Lamanya Waktu Pengeringan untuk Penetapan Kadar Air Pakan Metode Oven dalam Praktikum Analisis Proksimat - Bagus Djuni Ahadi; Mohammad Yasir Effendi (Jurnal Ilmu Peternakan Terapan, 2019)
The purpose of the study was to determine the length of drying time to achieve constant weight in the process of determining the water content of the feed by the oven method in the proximate analysis. This treatment were drying with 105oC (drying time 4, 5, 6, 7, 8 hours and or until a constant weight was reached) and 110oC (drying time 2, 3, 4, 5, 6 hours and or until a constant weight was reached ) for 5 types of samples that had water content of â‰¤14%, including: BR1, broiler concentrate (KBr), cracked corn, rice bran and soybean meal. The data analysis was the average of treatments that repeated 5 times on 5 sample types. The results of this study concluded that to determine the water content by the oven method on feed and feed ingredients that had water content â‰¤14% required an optimum drying time for 6 hours at 105oC and 4 hours at 110 oC.Â